Screening interactions of zinc phthalocyanine-PPV oligomers with single wall carbon nanotubes - A comparative study - Bartelmeß, Jürgen; Ehli, Christian; Cid, Juan-Jose; Garcia-Iglesias, Miguel; Vazquez, Purificacion; Torres, Tomas; Guldi, Dirk Michael (Journal of Materials Chemistry, 2011)
In this paper, the ability to disperse single wall carbon nanotubes (SWNT) of several different-nature poly(p-phenylene vinylene) (PPV) oligomers having pendant zinc phthalocyanines (ZnPc) has been investigated. Based on the quenching of the ZnPc and SWNT fluorescence in the supramolecular assemblies, it has been shown that parameters such as p/n-type character of the oligomer, size and the distance between the ZnPc moiety and the conjugated backbone play an important role in the strength of the interactions. Important results suggest that n-type oligomers as well as certain flexibility in the phthalocyanine arrangement are breakthroughs for immobilizing SWNT in THF, affording stable and homogeneous suspensions. Transient absorption measurements confirm that upon photoexcitation the photoexcited ZnPc triggers an intraensemble charge transfer to yield oxidized ZnPc and reduced SWNT. © 2011 The Royal Society of Chemistry.